Punishments in the Crimes against Patrimony matter - Moise, Andrei Emil (Technium Social Sciences Journal, 2023)
In the process of drafting the law and, subsequently, in its application, the principle of legality of incrimination requires compliance with certain conditions. Because of this, in the process of creating the law, it is mandatory that depending on the social realities, the legislator to incriminate deeds of certain gravity, committed over time, facts that raise the issue of risk and fear that they could repeat, endangering or even harming social values that must be protected by criminal law. Articles 228-230 of the National Criminal Code go beyond prohibition of the retrospective application of criminal is susceptible of several meanings, these terms or expressions will be explained even in the law, as the case may be, in the General Part or in the Special Part of the Criminal Code. The court has the obligation to comply with the criteria for individualizing the sentence, as well as the methods of execution as they were provided by law. These principles are held together by the importance of preserving the values of patrimony and to sustain the base principles of the Constitution and even the Human Rights Carta.